Experimental approach on the contribution of wind and animal vectors in the dispersal and colonization of testate amoebae (Protista, Amoebozoa) in freshwater ecosystems - Matheus Henrique de Oliveira de Matos; Felipe Rafael de Oliveira; Fernando Miranda Lansac-Tôha; Melissa Progênio; Bianca Ramos de Meira; Loiani Oliveira Santana; Crislaine Cochak; Luiz Felipe Machado Velho (Acta Limnologica Brasiliensia)
Abstract: Aim We aimed to understand how testaceous amoebae spread in new sites, assessing their dispersal potential by wind and animals in freshwater ecosystems. Methods We conducted a field experiment over 33 days between July and August 2018. The study included four different approaches: (i) a control group exposed exclusively to wind, (ii) the addition of propagules dispersed by Odonata (aquatic insects), (iii) the addition of propagules dispersed by amphibians, and (iv) the combined addition of propagules of both animals. Results We detected a total of 13 species of testate amoebae. Regarding species richness, we observed a steady increase throughout the experimental period. In terms of abundance, a similar trend was observed, with differences in the treatment of all vectors combinated, when comparing the treatments with only wind, and the combination of wind and vectors alone, indicating a possible progressive colonization of these organisms in the new aquatic environment. Regarding the composition of testate amoebae, we did not detect significant differences between treatments within each period or between different treatments throughout the experiment. Conclusions Our results demonstrate the importance of animal vectors in the transport of testate amoebae cysts.